Review on Treatment of Gout & Hyperuricemia - Chowdhury, MR; Hassan, MM; Hakim, F; Haq, SA (Journal of Bangladesh College of Physicians and Surgeons, 2011)
In the last few decades, both hyperuricemia and gout have increased markedly. Recent studies show new concept into the transporters that handle uric acid in the kidney as well as possible links between these transporters & hyperuricemia. There are changes in the treatment of established hyperuricemia. Febuxostat and PEGuricase are two novel treatments that have been evaluated and shown to be highly effective in the management of hyperuricemia. Monosodium urate (MSU) crystals are the inducers of inflammation. Within the joint, they trigger a local inflammatory reaction, neutrophil recruitment, and the production of proinflammatory cytokines as well as other inflammatory mediators. The uptake of MSU crystals by monocytes involves interactions with components of the innate immune system. The inflammatory effects of MSU are IL-1-dependent and can be blocked by IL-1 inhibitors. These advances in the understanding of hyperuricemia and gout provide new therapeutic targets for the future. DOI: http://dx.doi.org/10.3329/jbcps.v29i2.7953 (J Bangladesh Coll Phys Surg 2011; 29: 85-95)